Research priorities in Bangladesh: analysis of crop production trends (SAARC Journal of Agriculture, 2014)
Agriculture in Bangladesh is at a stage where there is a need for research priority setting. Given the physical, financial and human resource base, there is a need for proper allocation of these resources for higher and sustainable growth in production and productivity. On the other hand, resource allocation is needed to be distributed based on the commodity and regional importance. The study generates indices of research priorities for the crop sector of Bangladesh in terms of commodities and regions keeping in view the national developmental goals. Growth rates were calculated and compared share of different sectors, commodities were used to determine the priorities which is basically initial base of the congruence analysis method. Literature survey was carried out to understand the priorities at different point of times given the grand realities based on the secondary data. Division wise share analysis was done to determine the regional priority. The study concludes and emphasizes the need for (a) the increased allocation in agricultural research (b) strengthening of rice research activities (c) proportional allocation of research budget for pulses, oilseeds, cash crops, fruits and vegetables, (d) reduction of improper trade balance in export-import, and (e) regional importance for research resource allocation.DOI: http://dx.doi.org/10.3329/sja.v11i1.18375 SAARC J. Agri., 11(1): 53-70 (2013)